Dual stimulation of antigen presenting cells using carbon nanotube-based vaccine delivery system for cancer immunotherapy. (October 2016) - Hassan, Hatem A.F.M.; Smyth, Lesley; Wang, Julie T.-W.; Costa, Pedro M.; Ratnasothy, Kulachelvy; Diebold, Sandra S.; Lombardi, Giovanna; Al-Jamal, Khuloud T.
Abstract: Although anti−cancer immuno−based combinatorial therapeutic approaches have shown promising results, efficient tumour eradication demands further intensification of anti−tumour immune response. With the emerging field of nanovaccinology, multi−walled carbon nanotubes (MWNTs) have manifested prominent potentials as tumour antigen nanocarriers. Nevertheless, the utilization of MWNTs in co−delivering antigen along with different types of immunoadjuvants to antigen presenting cells (APCs) has not been investigated yet. We hypothesized that harnessing MWNT for concurrent delivery of cytosine−phosphate−guanine oligodeoxynucleotide (CpG) and anti-CD40 Ig (αCD40), as immunoadjuvants, along with the model antigen ovalbumin (OVA) could potentiate immune response induced against OVA−expressing tumour cells. We initially investigated the effective method to co−deliver OVA and CpG using MWNT to the APC. Covalent conjugation of OVA and CpG prior to loading onto MWNTs markedly augmented the CpG−mediated adjuvanticity, as demonstrated by the significantly increased OVA−specific T cell responses in vitro and in C57BL/6 mice. αCD40 was then included as a second immunoadjuvant to further intensify the immune response. Immune response elicited in vitro and in vivo by OVA, CpG and αCD40 was significantly potentiated by their co−incorporation onto the MWNTs. Furthermore, MWNT remarkably improved the ability of co−loaded OVA, CpG and αCD40 in inhibiting the growth of OVA−expressing B16F10 melanoma cells in subcutaneous or lung pseudo−metastatic tumour models. Therefore, this study suggests that the utilization of MWNTs for the co−delivery of tumour−derived antigen, CpG and αCD40 could be a competent approach for efficient tumours eradication.